Adolescents’ Understanding of Their Rights and Experiences of Autonomy - McCluskey E; O'Neill J (Pennsylvania State University, 2021)
Article 42 of the United Nations Convention on the Rights of the Child (UNCRC) states that children’s rights must be widely known by children and adults alike. Research on children’s rights has found that children and adolescents often have limited or incorrect knowledge and understandings of rights and how they apply to their everyday lives. Despite New Zealand ratifying the convention in 1993 it appears that children may continue to have little knowledge about rights. This research explored adolescents’ knowledge and understanding of their rights and UNCRC, where their knowledge and understanding come from, and how student experiences of autonomy may influence these understandings. Semi-structured interviews were used with 10 secondary (high) school students aged 14-15. Thematic analysis revealed that students may still hold limited and varied knowledge and understanding of their rights, and sources of this knowledge include inconsistent education at school, and television. It was also found that rights may not be a common discourse among adolescents. Teacher and government responsiveness towards adolescent students, and choices offered to them appeared to have an impact on student experiences of autonomy. These findings could have important implications for government policy and legislation, and rights education within New Zealand schools.